Occurrence of aflatoxins in milk and their effects on reproduction - KOUROUSEKOS (Γ. Δ. ΚΟΥΡΟΥΣΕΚΟΣ), G. D.; LYMBEROPOULOS (Α. Γ. ΛΥΜΠΕΡΟΠΟΥΛΟΣ), A. G. (Journal of the Hellenic Veterinary Medical Society, 2017)
The aflatoxins are toxic metabolites of the fungi Aspergillus flavus and Aspergillus parasiticus. These fungi invade the forages and under suitable conditions produce aflatoxins (Bl, B2, Gl, G2). The consumption of aflatoxins by the animals results in various pathological conditions (aflatoxicoses), with symptoms that vary depending on the species of animal, the age, the degree of forage invasion by the fungi and the quantity of the consumed feed. Nowadays, researchers pay more attention to the aflatoxins, because the latter do occur in many parts of the world. The regions more affected by aflatoxins are those with tropic or subtropic climate, since the levels of humidity and temperature play an important role in fungi's growth. The consumption of anatoxin Bl results in the excretion of aflatoxin Ml into the milk. Ml is one of Bl's metabolites and in some cases it is detected in concentrations higher than the maximum desirable limits fixed by each state, making the milk inappropriate for consumption. Furthermore, there are many reports about the effects of aflatoxins on the reproductive system. Sexual maturation, growth and maturation of the follicles, levels of hormones, gestation, growth of foetus are some of the parameters that are possibly influenced by aflatoxins. Regarding the genital system of male, most reports are related with the likely effect of aflatoxins on the size and weight of the genital organs, on spermatogenesis, on the number and morphology of spermatozoa, as well as on the levels of hormones.